Predicting the monitoring/reading of communications on a smartphone among young drivers using an extended theory of planned behaviour. (March 2020) - Murphy, Georgia; Gauld, Cassandra; Lewis, Ioni
Highlights: The TPB was significant when predicting both intention and behaviour Habit, mindfulness and cognitive capture were significant predictors of intention Intention was the only significant predictor of behaviour Abstract: Australian drivers aged 17–25 years are overrepresented in road crashes, with many crashes resulting from smartphone use. The current study, based on a prospective design and an extended TPB framework, predicted young drivers' intentions to, and actual behaviour of, monitoring/reading social interactive technology via a smartphone while driving. An online survey at Time 1 (N = 167) assessed the TPB constructs of attitude, subjective norm and perceived behaviour control (PBC), and the additional factors of habit, mindfulness and cognitive capture. A hierarchical multiple regression analysis showed that the TPB constructs accounted for 76.4% in the variance of young drivers' intentions. The extended model, which included habit, mindfulness and cognitive capture accounted for a significant 79% of the variance in intention, and these additional factors explained a significant amount of variance over and above the TPB constructs. The Time 2 survey (N = 95) assessed actual behaviour in relation to smartphone use in the one-week period between the Time 1 and 2 surveys. Results from a multiple regression analysis of Time 2 found that, as expected, intention was a significant predictor of the behaviour of monitoring/reading a smartphone while driving. The results support the TPB for predicting intention and actual behaviour in relation to monitoring/reading a smartphone while driving. The theoretical and practical implications of the current study are discussed as well as recommendations for future research.